2008
DOI: 10.30970/cma1.0051
|View full text |Cite
|
Sign up to set email alerts
|

Cluster structure in Al-Si eutectic melt with solid Ni particles

Abstract: The structure of liquid Al 0.88 Si 0.12 eutectic alloy upon addition of Ni powder was studied by means of X-ray diffraction. The main structure parameters as a function of the Ni-content were analyzed. It is shown that the atomic distribution in these alloys is inhomogeneous, revealing the existence of chemically ordered structural units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Concurrently, Al oxidation might have played a similar role. The melting temperatures for pure Al and the Al-Si eutectic system are 660.35 • C and 577 • C, respectively [29]. Al 2 O 3 formation can occur above 500 • C at the CVD chamber pressure (0.01 Torr).…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, Al oxidation might have played a similar role. The melting temperatures for pure Al and the Al-Si eutectic system are 660.35 • C and 577 • C, respectively [29]. Al 2 O 3 formation can occur above 500 • C at the CVD chamber pressure (0.01 Torr).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, competition between aluminum and silicon atoms in their interaction with nickel can affect the process of structure formation in ternary melts. It was shown in Mudry and Shtablavyi (2008) that Al-Ni and Al 3 Ni-like chemical ordering mainly determines the structure features in (Al-Si) 1 − x Ni x alloys. Moreover, the chemically ordered structure groups can become the nuclei of intermetallic phases during crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the dependence of the value of structural parameter in liquid on the copper content in the alloy and temperature showed that the alloy eutectic composition (Al83Cu17) reduces the structural parameter in liquid in the temperature range 1023 -1253 K, and the presence of sharp peak indicates an ordered structure [9]. In [10], the peak was observed in the range of temperatures 835 -935 K. The authors of [9][10][11][12] notes, that slight overheating of alloys above the liquidus line leads to a significant reduction of complexes in a liquid. It is known that an increase in the cooling rate to 10 4 -10 5 K/s leads to the formation of a supersaturated solid solution and an increase in the content of the Al2Cu phase in a nonequilibrium eutectic [13][14].…”
Section: Introductionmentioning
confidence: 99%